Страсна свічка як оберіг гончарів Чернігівщини та її семантика - Рахно, К. (Сiверянський лiтопис, 2016)
Страсна свічка слугувала у гончарів Чернігівщини оберегом при випалюванні. За її допомогою вони впливали на полум’я гончарного горна. У статті аналізуються витоки страсної свічки як оберега, її символічне значення й семантика в слов’янській календарній обрядовості, звичаєвості й магії, зв’язок із язичницьким культом Перуна. Страстная свеча служила у гончаров Черниговщины оберегом при обжиге. С её помощью они влияли на пламя гончарного горна. В статье анализируются истоки страстной свечи как оберега, её символическое значение и семантика в славянской календарной обрядности, обычаях и магии, связь с языческим культом Перуна. The burning of earthenware in Ukraine in the early 20th century was traditionally accompanied by magic actions, in what a potter himself appeared as an proactive principle. He made special efforts to regulate the fire element, to take it under his control. For all those different apotropaic devices were used. For example, craftsmen, originated from Oleshnya in the Chernigov Region – with the flame of a Maundy Thursday candle cross signs have been made on a potter’s wheel and on the ware compartment of a kiln, before the beginning and at the end of burning the kiln was crossed as well without fail. Maundy Thursday candles was used among the potters of Chernigov Region as a charm during the firing of earthenware. They influence on the flame of pottery kiln with their help. Fire in pottery kiln was imagined to be identical to a lightning of Perun, sacred lightning flame, what differed from the terrestrial fire by its characteristics. Its demiurgical potential could constitute danger. Therefore it has to influence on it with the same magical means, which were used for the protection against storm and thunder in the traditional culture of the Slavs. These are things-signs, things-concepts. In the same capacity they were assimilated by the Christian religion. The origins of a Maundy Thursday candle as a charm, its symbolic meaning, and semantics in Slavic ceremonies, customs, and magic, relations with the pagan cult of Perun are analysed in the article.